A note on homoclinic solutions of (p, q)-Laplacian difference equations. Issue 3 (4th March 2019) - Nastasi, Antonella; Vetro, Calogero
Abstract : We prove the existence of at least two positive homoclinic solutions for a discrete boundary value problem of equations driven by the( p, q ) -Laplace operator. The properties of the nonlinearity ensure that the energy functional, corresponding to the problem, satisfies a mountain pass geometry and a Palais–Smale compactness condition.